Progress in the knowledge of 'ruby silvers': New structural and chemical data of pyrostilpnite, Ag3SbS3. (4th June 2020) - Biagioni, Cristian; Zaccarini, Federica; Roth, Philippe; Bindi, Luca
Abstract: The crystal structure of pyrostilpnite from the Plaka mine, Lavrion Mining District, Greece, was refined in the space group P 21 / c to a final R 1 index of 0.0283 on the basis of 2047 reflections with F o > 4σ( F o ) and 65 refined parameters. Unit-cell parameters of the crystal examined are a = 6.8629(6), b = 15.8800(14), c = 6.2711(5) Å, β = 117.087(2)°, V = 608.48(9) Å 3 and Z = 4. Chemical data agree with the stoichiometric formula Ag3 SbS3 . The crystal structure reported previously was confirmed, although a higher precision of refinement was achieved. It can be described as formed by 010 slabs running along c and connected along a through relatively longer Ag–S bonds. The analysis of the atomic displacement parameters together with a refinement with higher order tensors in the expression of the structure factors revealed no hint for pyrostilpnite as an ionic conductor. A historical background of the 'ruby silvers' is also reported.